The association of indoxyl sulfate with fibroblast growth factor‐23 in cats with chronic kidney disease - Liao, Yu‐Lun; Chou, Chi‐Chung; Lee, Ya‐Jane (Journal of veterinary internal medicine, 2019)
Background Indoxyl sulfate (IS) has been reported not only to increase with the severity of impaired renal function, but also possibly to be a factor associated with bone abnormalities linked to fibroblast growth factor‐23 (FGF‐23) in humans with chronic kidney disease (CKD). It is not yet known whether this correlation between IS and FGF‐23 holds true for cats with CKD. Hypothesis Accumulation of IS is related to FGF‐23 secretion in cats with CKD. Animals Twenty clinically healthy cats and 73 cats with CKD cases were evaluated retrospectively. Methods The concentrations of IS and FGF‐23 in plasma were determined by high‐performance liquid chromatography and ELISA, respectively. Progression was defined as an increment of 0.5 mg/dL of serum creatinine concentration within 3 months. Results Plasma IS and FGF‐23 concentrations were significantly increased concurrently with decreasing renal function. Higher concentration of FGF‐23 was significantly associated with higher concentration of IS after adjusting for various confounding factors including creatinine and phosphate. Furthermore, the correlation between IS and phosphate was higher than that between FGF‐23 and phosphate. When the renal progression group was compared with the non‐progression group, both IS and FGF‐23 were found to be significantly increased (P < .05). In addition, the area under receiver operator curve of the combination of IS and FGF‐23 predicted renal progression at a level >0.9. Conclusions and Clinical Importance Both FGF‐23 and IS are associated with phosphate metabolism and CKD progression.